The Clinical Effectiveness of a Physiotherapy Delivered Physical and Psychological Group Intervention for Older Adults With Neurogenic Claudication: The BOOST Randomized Controlled Trial. Issue 8 (12th March 2022) - Williamson, Esther; Boniface, Graham; Marian, Ioana R; Dutton, Susan J; Garrett, Angela; Morris, Alana; Hansen, Zara; Ward, Lesley; Nicolson, Philippa J A; Rogers, David; Barker, Karen L; Fairbank, Jeremy C; et al.
Abstract: Background: Neurogenic claudication (NC) is a debilitating spinal condition affecting older adults' mobility and quality of life. Methods: A randomized controlled trial of 438 participants evaluated the effectiveness of a physical and psychological group intervention (BOOST program) compared to physiotherapy assessment and tailored advice (best practice advice [BPA]) for older adults with NC. Participants were identified from spinal clinics (community and secondary care) and general practice records and randomized 2:1 to the BOOST program or BPA. The primary outcome was the Oswestry Disability Index (ODI) at 12 months. Data were also collected at 6 months. Other outcomes included ODI walking item, 6-minute walk test (6MWT), and falls. The primary analysis was intention-to-treat. Results: The average age of participants was 74.9 years (standard deviation [ SD ] 6.0) and 57% (246/435) were female. There was no significant difference in ODI scores between treatment groups at 12 months (adjusted mean difference [MD]: −1.4 [95% confidence intervals (CI) −4.03, 1.17]), but, at 6 months, ODI scores favored the BOOST program (adjusted MD: −3.7 [95% CI −6.27, −1.06]). At 12 months, the BOOST program resulted in greater improvements in walking capacity (6MWT MD: 21.7m [95% CI 5.96, 37.38]) and ODI walking item (MD: −0.2 [95% CI −0.45, −0.01]) and reduced falls risk (odds ratio: 0.6 [95% CI 0.40, 0.98]) compared to BPA. No serious adverse events were related to either treatment. Conclusions: The BOOST program substantially improved mobility for older adults with NC. Future iterations of the program will consider ways to improve long-term pain-related disability. Clinical Trials Registration Number: ISRCTN12698674